2023
DOI: 10.3390/s23020889
|View full text |Cite
|
Sign up to set email alerts
|

Extended Tromograph Surveys for a Full Experimental Characterisation of the San Giorgio Cathedral in Ragusa (Italy)

Abstract: Geophysical surveys are widely used to reconstruct subsoil seismo-stratigraphic structures with a non-invasive approach. In this study the geophysical surveys were carried out with the aim to characterise the San Giorgio Cathedral in Ragusa (Italy) and the area on which it is built from a dynamic point of view. A 3D subsoil model was realised through the integration of two active (i.e., seismic tomography and multichannel analysis of surface waves) and one passive seismic technique (horizontal to vertical spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This produces signals with low amplitude and high levels of noise, which affect the identification of higher modes, commonly local and more sensitive to damage, limiting the investigated bandwidth to a few hertz [45,47,48]. Moreover, the dynamic response of the built CH is commonly governed by its components and macro-elements, which are complex to identify through ambient vibration and could be evident only at specific measurement points [49,50]. Finally, it is worth noting that the intrusiveness of the sensing systems to the view and their obstructiveness for operation should be minimised, especially for long-term monitoring, as with any other measures affecting CH fruition, aesthetics, and heritage value [47,51,52].…”
Section: Preventive Conservation Paradigm: Advantages and Open Challe...mentioning
confidence: 99%
“…This produces signals with low amplitude and high levels of noise, which affect the identification of higher modes, commonly local and more sensitive to damage, limiting the investigated bandwidth to a few hertz [45,47,48]. Moreover, the dynamic response of the built CH is commonly governed by its components and macro-elements, which are complex to identify through ambient vibration and could be evident only at specific measurement points [49,50]. Finally, it is worth noting that the intrusiveness of the sensing systems to the view and their obstructiveness for operation should be minimised, especially for long-term monitoring, as with any other measures affecting CH fruition, aesthetics, and heritage value [47,51,52].…”
Section: Preventive Conservation Paradigm: Advantages and Open Challe...mentioning
confidence: 99%
“…Consequently, this approach can lead to inaccuracies in determining the predominant frequency of the microtremor spectrum, making it challenging to estimate the site amplification factor [ 11 ]. On the other hand, numerous studies have demonstrated that the microtremor horizontal-to-vertical spectral ratio method (HVSR) effectively eliminates the influence of the vibration source on the site dynamics analysis, resulting in predominant frequencies that are more representative of the actual site frequencies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. As a consequence, many recent studies have employed the microtremor HVSR method to determine the site characteristic parameters.…”
Section: Introductionmentioning
confidence: 99%